Quality Impact Analysis Website User Satisfaction Method Based WebQual 4.0 On Website Stikom Surabaya - Erisaputra, Purba; Sulistiowati, Sulistiowati; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Institute for Business and Information Stikom hereinafter referred Stikom Surabaya Surabaya is a private university based Information Technology (IT). To support the development of this campus then made a website as a media introduction and means of information for students Stikom Surabaya. But the problems that occurred during this ranking website where Stikom Surabaya far behind compared with campuses in Indonesia and ranks 52 campuses throughout Indonesia. The aim of this study was to look into the matter by analyzing the relationship between the quality of the website (Website Quality) and customer satisfaction (Customer Satisfaction). From questionnaires conducted obtained a sample of 127 respondents. Data from the questionnaire testing the variables with the validity and reliability. The next test and test data normality assumption as a condition for the implementation of the next step, namely multiple linear regression analysis. Based on the results of this test showed that the variable quality of use (usability), the quality of information (information quality), and the quality of interaction (interaction quality) positive and significant impact on customer satisfaction (customer satisfaction) with a coefficient of determination of (26,213) > F table (3,07).